Nitric oxide role in development of the endothelial dysfunction in diabetic foot syndrome - Bilyayeva, O. O.; Kozynets, H. P.; Osadcha, O. I.; Kryzhevskyy, Ye. Ye.; Knivets, M. A. (Modern medical technology, 2019)
Introduction. Diabetes mellitus causes many acute and chronic complications, including diabetic foot syndrome (DFS) – a serious complication that can be a test for patients and directly affect their quality of life. One of the most effective treatments for DFS is the use of nitric oxide (NO). The main advantage of using NO-therapy is the effect of polyfunctional nitrogen monoxide on all phases of purulent-inflammatory process. Purpose of the study. The nitric oxide effect features on the development of endothelial dysfunctions in patients with diabetic foot syndrome are explored. Materials and methods. In the department of purulent surgery at Kyiv City Clinical Hospital No. 6 in 2019 from January to June, 76 patients with DFS in stages II–V were treated by F. Wagner. In 47 (61.8%) patients the neuropathic form of DFS was observed, and 29 (38,2%) were neuroichemic form. According to the DFS rates of F. Wagner patients were distributed: II – 24 (31,7%) patient, III – 29 (38,1%) patient, IV – 15 (19,7%) and V stages – 8 (10,5%). All patients were studied in the capillary zone of necrotic lesions of the content of NO, the activity of superoxide dismutase (SOD). Results and discussion. The signaling role of NO in cells is highly dependent on the level of superoxide. The balance between systems that synthesize NO and superoxide determines the regulatory orientation of the signals, and its disruption contributes significantly to inflammation in diabetes. Conclusions. The use of NO-therapy helps to optimize the processes of regulation of the induction of nitric oxide and to improve the clinical results in the treatment of diabetic foot syndrome.